Microsoft Windows - Alcianno G. Gani (JURNAL MITRA MANAJEMEN, 2016)
AbstractMicrosoft Windows (or simply Windows) is a metafamily of graphical operating systems developed, marketed, and sold by Microsoft. It consists of several families of operating systems, each of which cater to a certain sector of the computing industry. Active Windows families include Windows NT, Windows Embedded and Windows Phone; these may encompass subfamilies, e.g. Windows Embedded Compact (Windows CE) or Windows Server. Defunct Windows families include Windows 9x and Windows Mobile. KeyWords : Windows, Microsoft, Microsoft Windows, Operating system